Effect of eclampsia on pregnancy outcome at tertiary care center, Gujarat, India - Patel, Nidhi; Shah, Sumant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia, a common medical emergency of pregnancy mainly seen in 5% to 10% of all pregnancies. The objective of the present study was to study the effect of eclampsia on maternal and perinatal outcome. Methods: This cross-sectional study was conducted among 50 clinically diagnosed women with eclampsia in their third trimester of pregnancy. Inclusion criteria for the study was; females with singleton pregnancy, all in the third trimester which were diagnosed to have PIH based on the development of hypertension for the first time, proteinuria with or without edema, with no history of previous urinary tract troubles and no evidence of UTI. Results: Almost 84.0% participants were belonged to age group of 20 to 30 years age, 54.0% were belonged to rural area and 92.0% were belonged to lower socio-economical class, 88.0%% participants were registered as emergency case, 34.0% participants were stayed more than 10 days at hospital and 36.0% were completed ANC visit. Almost 24.0% participants were anemic, 6.0% pre-eclampsic and 4.0% have tween pregnancy. Severe hypertension at the time of admission were noted in 50.0% participants followed by absent knee jerk (12.0%), proteinuria (78.0%) and edema (62.0%) respectively. Maternal mortality and still birth observed in 2.0% and 18.0% cases respectively. Conclusions: Early age, lower socio-economic class, anemia, less ANC clinic visit, higher hospital stay and primigravida observed more among study participants and these factors may play an important role in the pathogenesis of eclampsia.